Rapid and high biodegradation of phenols catalyzed by Candida tropicalis NCIM 3556 cells - Varma, Rita J.; Gaikwad, Bhaskar G. (Enzyme and Microbial Technology, 2008)
Cells of 19 yeast cultures, belonging to genus Candida were screened for biodegradation of phenol. The cultures procured from NCIM culture collection and were selected so as to contain a representative of varied strains of the species. These were grown in MGYP3 medium and tested for biodegradation of phenol. C. tropicalis (CT) nos. 3118, 3556 and C. lipolytica 3472 effectively degraded >90% 2 g l(-1) phenol. The C. tropicalis 3556 strain was selected for further studies as it metabolized >95% phenol in just 16 h as compared to the other two which took 48 h. The maximum substrate concentration that could be completely degraded was 2 g l(-1). A study of induction, of different concentration of phenol in the growth medium showed that toxicity to cell growth increased with increasing phenol levels in growth media. Biodegradation of phenol derivatives - o-cresol, m-cresol. 2,6-dimethyl phenol, alpha-naphthol, o-chlorophenol and p-nitrophenol, by the selected three strains indicated that the specificity of each culture varied for different substrate. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Biodegradation; Candida lipolytica; Candida tropicalis; phenol; Phenol derivatives

Biodegradation and phenol tolerance by recycled cells of candida tropicalis NCIM 3556 - Varma, R. J.; Gaikwad, B. G. (International Biodeterioration & Biodegradation, 2009)
Resting cells of Candida tropicalis NCIM 3556 rapidly degraded almost completely 2 g L(-1) phenol in 16h. In this study, we explored the possibility of further increasing the efficiency of the culture by repeatedly reusing the cell for biodegradation. The effect of continuous recycling of whole cells of C. tropicalis, for biodegradation of phenol indicated that though with each recycle of the cell there was steady decline in phenol biodegradation the conversion was appreciable for five recycle (similar to 70%) and reached half-life of 50% after eleven recycles. Inhibition due to substrate, recycling of cells and adaptation of residual cell were estimated and an equation derived; which indicated that the cell resilience to phenol increased with each cycle and at the end of eleven recycle adaptation was 68%. However, when the adapted cells were sub cultured and showed marginal increase <10% in biodegradation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Candida tropicalis; Inhibition; phenol; Recycle; Tolerance

Continuous phenol biodegradation in a simple packed bed bioreactor of calcium alginate-immobilized Candida tropicalis (NCIM 3556) - Varma, R. J.; Gaikwad, B. G. (World Journal of Microbiology & Biotechnology, 2010)
Phenol biodegradation in a continuous system of immobilized Candida tropicalis NCIM 3556 was studied. The bioreactor was simple, it had a feed inlet from the bottom and the effluent outlet from top, no supplementary oxygen was supplied, the reactor was operated continuously for 116 days. Initially the column was run continuously with a feed concentration of 2 g l(-1) for 42 days whence a degradation of > 97% was achieved. The feed concentration was then increased to 3 g l(-1), for which a similar to 80% biodegradation was sustained for 90 days after which there was a steady decrease in the performance. When the phenol degradation was reduced to similar to 50% in 116 days, the reactor was stopped. The efficiency of free cells recycled every 24 h and immobilized cells were compared; it was estimated that repeated reuse of free cells in batch mode gave an overall efficiency of 0.102 g phenol degradation g(-1) cell wet weight in 12 days. In contrast, the immobilized system of the same biomass had a longer working lifetime of similar to 4 months indicating an efficiency of 3.72 g phenol g(-1) cell wet wt.
Keywords: Biodegradation; Ca alginate; Candida tropicalis; Immobilization; phenol